Community, state, and market on the North Atlantic rim: challenges to modernity in the fisheries - Apostle, Richard (Studies in Comparative Political Economy and Public Policy, 1998)
Examines the implications of common market integration, privatized resource management, and small business development policies for fishery-dependent communities in terms of long-term sustainability and participatory democracy.